Subharmonic Oscillations and Chaos in DC-DC Switching Converters - Pikulin, D. (Elektronika ir Elektrotechnika, 2013)
In this paper we have demonstrated the applicability of numerical path-following approach to the analysis of bifurcation behaviour and subharmonic oscillations in switch-mode DC-DC converters. The method developed in this research allows plotting the complete bifurcation diagrams on the parameter space that can provide useful practical information for engineers to determine the complex behaviour of SMPS. In particular, we have provided specific complete bifurcation diagrams for the current controlled boost converter and discussed the key features of the interaction of smooth and non-smooth bifurcation phenomena. DOI: http://dx.doi.org/10.5755/j01.eee.19.4.4054